Induction of Secondary Metabolites from the Marine-Derived Fungus Aspergillus versicolor through Co-cultivation with Bacillus subtilis - Abdel-Wahab, Nada M.; Scharf, Sebastian; Özkaya, Ferhat C.; Kurtán, Tibor; Mándi, Attila; Fouad, Mostafa A.; Kamel, Mohamed S.; Müller, Werner E. G.; Kalscheuer, Rainer; Lin, Wenhan; Daletos, Georgios; Ebrahim, Weaam; Liu, Zhen; Proksch, Peter (Planta Medica, 2019)
A new cyclic pentapeptide, cotteslosin C (1), a new aflaquinolone, 22-epi-aflaquinolone B (3), and two new anthraquinones (9 and 10), along with thirty known compounds (2, 4 – 8, 11 – 34) were isolated from a co-culture of the sponge-associated fungus Aspergillus versicolor with Bacillus subtilis. The new metabolites were only detected in the co-culture extract, but not when the fungus was grown under axenic conditions. Furthermore, the co-culture extract exhibited an enhanced accumulation of the known constituents versicolorin B (14), averufin (16), and sterigmatocyctin (19) by factors of 1.5, 2.0, and 4.7, respectively, compared to the axenic fungal culture. The structures of the isolated compounds were elucidated on the basis of 1D and 2D NMR spectra and mass spectrometry as well as by comparison with literature data. The absolute configuration of compounds 3, 9, and 10 was determined by ECD (electronic circular dichroism) analysis aided by TDDFT-ECD (time-dependent density functional theory electronic circular dichroism) calculations. Compounds 15, 18 – 21, and 26 exhibited strong to moderate cytotoxic activity against the mouse lymphoma cell line L5178Y, with IC50 values ranging from 2.0 to 21.2 µM, while compounds 14, 16, 31, 32, and 33 displayed moderate inhibitory activities against several gram-positive bacteria, with MIC values ranging from 12.5 to 50 µM.
Keywords: sponge-derived fungus; Aspergillus versicolor; cyclic pentapeptide; co-culture; ECD calculations; cytotoxicity; antibacterial activity